PENENTUAN DEBIT RENCANA SITU DENGAN METODA NRECA DAN NAKAYASU (Lokasi Universitas Indonesia, Depok) - Sudinda, Teddy W (Jurnal Air Indonesia, 2014)
Reservoir is one building that serves to store water, can be interpreted as a water reservoir in the surface soil from ground water or surface water. From the point of hydrology, it has various functions such as conservation of water resources, reduce the danger of flooding and drought. In this paper analyzed the average monthly discharge and flood discharge plans new reservoir in the Indonesia University area. Calculation of average monthly discharge in reservoir using the new calculation method the average monthly NRECA and evaporation that occurs in the study area. The calculation of flood discharge using hydrograph synthetic NAKAYASU taking into account the maximum daily rainfall and rainfall distribution.Ã‚Â Keywords: Flood Discharge, NRECA Method, NAKAYASU Hydrograph Method.